Clinical Presentation of Myocarditis in Children A Cross-Sectional Study (Medical Forum Monthly, 2024)
Objective: To evaluate the observational, diagnostic, and therapeutic characteristics of myocarditis in 150 children attending a tertiary care hospital.Study Design: A Cross-sectional study.Place and Duration of Study: This study was conducted at the Department of Paediatrics Medicine, University of Medical and Health sciences for women Nawabshah Sindh from 1st April 2022 to 30th September 2023.Methods: A descriptive letter survey was used in a sample of 150 children aged 1 month to 18 years with myocarditis. Information concerning symptoms, diagnostic tests, including echocardiography, levels of cardiac biomarkers, MRI, and treatment outcomes were obtained. Analysis of the collected data was done using the SPSS version 24.0 with a=(p< 0.05).Results: The age of the 150 patients ranged between 0 – 18 years with a mean age of 8.1 years and standard deviation of ± 3.9 years. Fatigue was reported by 72% of the patients, followed by shortness of breath in 68% and chest pain in 55%. Patients with heart failure were detected in 25% of cases. In combination with echocardiography, it was revealed that left ventricular systolic dysfunction was present in 82% of patients. At the onset of the obstructive sleep apnoea, developing patients experienced raised cardiac biomarkers by 88 percent. Of them 60% had a Cardiac MRI and out of those tested all were diagnosed of having myocarditis. Patients with heart failure had higher mortality than the rest (p = 0.03).Conclusion: It accordingly implies that myocarditis in children produces symptoms of a broad spectrum. The earlier the diagnosis, the better; in patients who have heart failure the prognosis is even better. Echocardiography and cardiac biomarkers are still useful, whereas other techniques as cardiac MRI are more accurate.